Legal Policy of Disparity in Sentencing as a Ground for Judicial Review in Indonesia Corruption Cases - Djatmika, Prija; Rahman, Wahbi; Wibowo, Dwi Edi; Weku, Robert Lengkong; Osman, Noor Dzuhaidah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Article 263 paragraph (2) of Law Number 8 of 1981 concerning the Criminal Procedure Code limits the grounds on which a Judicial Review of a court decision may be filed. This limitation stems from the extraordinary nature of the Judicial Review, as it provides a mechanism to reopen a case that has obtained permanent legal force (inkracht van gewijsde). Errors in assessing the grounds for a Judicial Review can undermine the principles of legal certainty and justice, which are fundamental to the rule of law. This paper analyzes the use of sentencing disparity in corruption cases as a basis for Judicial Review, as recognized by the Supreme Court of Indonesia. The study employs a normative-descriptive research method. The findings indicate that sentencing disparity in corruption cases is multi-causal, suggesting that it does not always constitute a factual matter but may also involve legal considerations. The study concludes that determining sentencing disparity as an instance of judicial error in a Judicial Review must be conducted with due regard to the principle of judicial independence. Furthermore, with the issuance of Supreme Court Regulation No. 1 of 2020 concerning Sentencing Guidelines under Articles 2 and 3 of the Corruption Eradication Law, issues of sentencing disparity should ideally be resolved through ordinary legal remedies such as appeals or cassation.